2007
DOI: 10.1111/j.1346-8138.2007.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of cutaneous Mycobacterium chelonae infection with roxithromycin

Abstract: Dear Editor, Mycobacterium chelonae is a rapidly growing mycobacterium that causes illnesses ranging from disseminated cutaneous infection, localized cellulitis, abscess, osteomyelitis, to catheter infection in immunocompetent or immunosuppressed patients. 1 Recent studies have shown that isolates of M. chelonae are usually susceptible to clarithromycin, 1,2 and thus it has been the drug of choice for cutaneous M. chelonae infection. 3 However, there have been case reports of clarithromycin resistance in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Obtaining in vitro susceptibilities is essential in directing treatment [ 8 ], but since it usually takes some time to obtain the antibiogram, suggested initial regimens include clarithromycin with the addition of imipenem, tobramycin or amikacin [ 12 , 14 ]. Many other newer antibiotics were successful in treating M. chelonae infections, like faropenem [ 13 ] and roxithromycin [ 15 ], and other treatment modalities should be considered in more recalcitrant or small lesions, such as surgical excision or cryotherapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining in vitro susceptibilities is essential in directing treatment [ 8 ], but since it usually takes some time to obtain the antibiogram, suggested initial regimens include clarithromycin with the addition of imipenem, tobramycin or amikacin [ 12 , 14 ]. Many other newer antibiotics were successful in treating M. chelonae infections, like faropenem [ 13 ] and roxithromycin [ 15 ], and other treatment modalities should be considered in more recalcitrant or small lesions, such as surgical excision or cryotherapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 outlines the recommended treatment for selected cutaneous NTM infections. 4,9,[11][12][13][14] Treatment guidelines need refinement, however clarithromycin is recommended as a first-line therapy. 15 To avoid acquired resistance a second agent should be added based on sensitivity testing, particularly for M. chelonae, although tolerability and multi-resistant organisms are limiting factors and further antibiotic development is needed.…”
Section: Discussionmentioning
confidence: 99%
“…A repeat biopsy is advised if treatment failure or relapse is suspected. Clarithromycin, minocycline, doxycycline, co-trimoxazole or combination of rifampicin and ethambutol for 3-6 months 9,13,14 Clarithromycin for 3-6 months (azithromycin or roxithromycin may also be considered); with addition of second antibiotic based on results of sensitivity testing to prevent acquired resistance 9,[11][12]…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the dose might have been insufficient, but the drug was thought to be ineffective because the eruption showed no changes after clarithromycin administration for 4 weeks. There are several similar reports in which initial clarithromycin treatment had no effect, 7 and an in vitro study showed that only 49% of M. chelonae clinical isolates are susceptible to this agent 8 . Thus, clarithromycin may not be a universal treatment for M. chelonae infection.…”
mentioning
confidence: 98%